Measurement and Determinants of Inclusive Growth: A Case Study of Pakistan (1990-2012) (The Pakistan Development Review, 2016)
Equality of opportunity is the core of inclusive growth, and the inclusive growth emphasises to create employment and other development opportunities through rapid and sustained economic growth, and to promote social justice and the equality of sharing of growth results by reducing and eliminating inequality of opportunity. The main objective of the study is to measure the inclusive growth first and then empirically examine its determinants. To measure the inclusive growth, we use the methodology developed by Asian Development Bank using weights and scores of different indicators. We develop a unified measure of inclusive growth, which integrates growth, inequality, accessibility and governance into one single measure. Results show that Pakistan is at satisfactory performance level with respect to its performance in growth inclusiveness. Further results of ARDL show that macroeconomic stability and social financial deepening are important determinants to enhance the inclusiveness, and reduce poverty and inequality, while reforms in trade sector are required to increase their efficiency in terms of inclusiveness. JEL Classification: O4 Keywords: Inclusive Growth, Poverty Reduction, Income Inequality, Equity, Accessibility, Social Protection